Religiosity, religious coping and psychological distress among Muslim university students in Malaysia - Mohd Hazreen Abdul Rashid; Nurul Azreen Hashim; Azlina Wati Nikmat; Mariam Mohamad (Institute of Advanced Engineering and Science, 2021)
High demands of academic life and social changes caused relatively high prevalence of psychological distress among university students compared to the general population. The aim of this study was to determine the prevalence of psychological distress among university students and to examine the factors associated with them. This was cross sectional study involving 467 Bachelor degree students from various faculties in Universiti Teknologi MARA. Participants were assessed using the Brief Religious Coping Scale (Brief RCOPE), the Hatta Islamic Religiosity Index 1996 (HIRS96) and the Depression, Anxiety and Stress Scale (DASS 21). This study highlighted relatively high prevalence of depression, anxiety, and stress among the students of UiTM Shah Alam. We also found consistent significant association between negative religious coping with both anxiety and depressive symptoms. Consistent with the earlier studies done among Muslim samples, the positive religious coping is not significantly associated with better psychological outcomes although only small effect was observed towards the depressive symptoms.